The concept of paradigm in Thomas Kunh and Edgar Morin: similarities and differences (Research, Society and Development, 2019)
The present article aimed to discuss the concept of paradigm in the thinking of Thomas Kuhn and Edgar Morin. In methodological terms, this study was carried out through a bibliographical research in scientific articles and books, being the qualitative data analysis approach. The research carried out evidenced the centrality of the paradigm concept for the works of Thomas Kuhn and Edgar Morin. In Kuhn's work the paradigm assumes a structuring function of the way phenomena are analyzed and understood. In Morin, this concept assumes a broad meaning, being understood as the matrix of Western thought. It was concluded that the main difference between the paradigm conceptualization for Morin and Kuhn is related to the comprehension of this concept. In relation to the similarities, both authors understand that scientific progress necessarily operates through the breaking and breaking of these models of explanation of reality, being even this the central proposal of the theory of the complexity developed by Edgar Morin.